Pencak Silat Sterlak: A Review in the Perspective of Historical Development in Bengkulu - Septian Raibowo; Oddie Barnanda Rizky; Andes Permadi; Andika Prabowo (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objectives. The traditional martial art of pencak silat is integral to our cultural heritage, passed down through generations. However, preserving its traditional values is under threat due to the influences of globalization and modern advancements. This research project aims to comprehensively analyze the evolution and current state of the traditional Sterlak Pencak Silat school in the Bengkulu province, shedding light on its historical significance and contemporary challenges. Materials and Methods. This research employs a qualitative approach to gather data. The study focuses on four college coaches in Bengkulu Province as the subjects of the research. The data collection methods used in this study include observation, interviews, and questionnaires. Results. The results of the observational research showed a value of 55.90%. The questionnaire results indicated that community knowledge was at 46%, categorized as moderate. The community preservation indicator yielded a result of 41.67%, also categorized as moderate. The interest indicator scored 48.13%, falling under the moderate category. The indicator for training activities obtained a result of 37.68%, categorized as low. The indicator for the role of government scored 35.42%, also categorized as low. Lastly, the indicator for facilities and infrastructure scored 35.94%, also categorized as low. Based on the research results, the development of the sterlak traditional pencak silat school in Bengkulu province is categorized as moderate. Conclusion. The Sterlak Traditional Pencak Silat School is currently in the process of development and has at least seven functions, including self-defense, art, entertainment, sports, religious, educational, and social functions. The community needs to make efforts to preserve and introduce Pencak Silat to the younger generation to maintain and protect the local culture of the region.